Bathymetric Control on Borchgrevink and Roi Baudouin Ice Shelves in East Antarctica - Eisermann, Hannes; Eagles, Graeme; Ruppel, Antonia Stefanie; Läufer, Andreas; Jokat, Wilfried; Eagles, Graeme; 1 Alfred Wegener Institute for Polar and Marine Research Bremerhaven Germany; Ruppel, Antonia Stefanie; 2 Federal Institute for Geosciences and Natural Resources Hannover Germany; Läufer, Andreas; 2 Federal Institute for Geosciences and Natural Resources Hannover Germany; Jokat, Wilfried; 1 Alfred Wegener Institute for Polar and Marine Research Bremerhaven Germany (Journal of Geophysical Research: Earth Surface, 2021)
The stability of ice shelves and drainage of ice sheets they buttress is largely determined by melting at their atmospheric and oceanic interfaces. Subglacial bathymetry can impact ice shelf stability because it influences the onset and the pattern of warm ocean water incursions into the cavities between them and the seafloor. Bathymetry is further important at pinning points, which significantly retard the flow of ice shelves. This effect can be lost instantaneously if basal and surface melting cause an ice sheet to thin and lift off its pinning points. With all this in mind, we have developed a model of bathymetry beneath the western Roi Baudouin and central and eastern Borchgrevink ice shelves in Dronning Maud Land based on inversion from gravity data and tied to available depth references offshore and subglacial topography inland of the grounding line. The model shows deep glacial troughs beneath the ice shelves and bathymetric sills close to the continental shelf. The central Borchgrevink Ice Shelf overhangs the continental slope by around 50 km, exposing its northern parts to the open ocean and higher ocean temperatures. Continuous troughs traverse the central Borchgrevink and western Roi Baudouin ice shelves at depths greater than the offshore thermocline and thus present a risk of Warm Deep Water intrusions into their cavities under the current and future oceanographic regimes. Differing bathymetric characteristics might explain the ice shelves' contrasting dominant mass loss processes. Plain Language Summary: The rate at which Antarctica's ice sheets flow off the continent is largely stabilized by floating ice shelves that form where they meet the surrounding ocean. Assessing the stability of this interconnected system strongly depends on correctly quantifying ice gain processes, such as snowfall, and ice mass loss processes, such as melting at the bases of the ice shelves. This basal melting strongly depends on the flow of warm ocean water into the cavity between the ice shelf and the seafloor below, ...